Distinctive roles of tumor necrosis factor receptor type 1 and type 2 in a mouse disc degeneration model - Shanzheng Wang (Elsevier, 2021)
Background: Elevated tumor necrosis factor alpha (TNF-α) expression is correlated with the progression of intervertebral disc degeneration (IVDD). Progranulin binding to tumor necrosis factor receptor (TNFR) and its derivative Atsttrin are effective for treating inflammatory arthritis. We hypothesize that Atsttrin has a protective effect in IVDD through different roles of TNFR receptor type 1 (TNFR1) and TNFR receptor type 2 (TNFR2) in degenerated discs. Methods: IVDD models were established in TNFR1−/−, TNFR2−/− mice and their control littermates. Nucleus Pulpous (NP) samples from human patients and IVDD murine models were evaluated by X-ray, micro-MRI, μCT, histological staining and immunofluorescence staining. NP cells isolated from wild-type (WT), TNFR1−/− and TNFR2−/− mice were treated with TNF-α or Atsttrin and then assayed by Western blotting, qRT–PCR, and ELISA. Results: TNFR1 and TNFR2 expression was significantly elevated in the disc tissues of both human patients and IVDD murine models. TNFR1 knockout contributed to reduced disc degeneration. In contrast, TNFR2 knockout was associated with enhanced IVDD severity, including degraded cellular composition, increased cell apoptosis and elevated vertebral destruction. Atsttrin protected against IVDD in WT and TNFR1−/− mouse models but had no effect in TNFR2−/− IVDD models. Additionally, in vitro NP cell-based assays demonstrated that TNF-α-stimulated catabolism and Atsttrin-activated anabolism depended on TNFR1 and TNFR2, respectively. Conclusion: TNFR1 is associated with the degenerative progression of IVDD, while TNFR2 contributes to the protective effect on the discs. Atsttrin protects against IVDD at least partially by inhibiting the TNFα/TNFR1 inflammatory/catabolic pathway and activating the TNFR2 protective/anabolic pathway. The translational potential of this article: This study demonstrates that TNFR1 and TNFR2 have disparate roles in disc degeneration and hlights the potential use of Atsttrin as a therapeutic agent against IVDD in mice.